Does More Generous Student Aid Increase Enrolment Rates into Higher Education? Evaluating the German Student Aid Reform of 2001 - Hans J. Baumgartner; Viktor Steiner (Deutsches Institut für Wirtschaftsforschung (DIW), 2006)
Students from low-income families are eligible to student aid under the federal students? financial assistance scheme (BAfoeG) in Germany. We evaluate the effectiveness of a recent reform of student aid that substantially increased the amount received by eligible students to raise enrolment rates into tertiary education. We view this reform as a ?natural experiment? and apply the difference-in-difference methodology using a discrete-time hazard rate model to estimate the causal effect on enrolment rates into higher education. We find that the reform had a small positive but statistically insignificant effect on enrolment rates.
Keywords: J24; H31; I22; I28; 330; educational transitions; educational finance; natural experiment and difference-indifference estimation